2023
DOI: 10.1177/1866802x231213384
|View full text |Cite
|
Sign up to set email alerts
|

Researching the Gap: Women in Latin American Political Science

Benjamin Goldfrank,
Yanina Welp

Abstract: This paper maps the gender balance in the discipline of political science in Latin America by examining data from 16 countries where we could find the number of female professors in political science departments (over 100 departments) as well as from 69 journals publishing political science research in Latin America and from 16 Latin Americanist journals in Canada, the United States, and Europe. We compare the proportion of female political science faculty members to the proportion of women serving as editors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The gender gap is not only limited to publications and university appointments. For example, in their study, Goldfrank and Welp (2023) examines women's marginalization in journal editorial boards in Latin American journals. They compare the representation of women on the editorial boards of several political science journals with the proportion of female faculty members in political science departments.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The gender gap is not only limited to publications and university appointments. For example, in their study, Goldfrank and Welp (2023) examines women's marginalization in journal editorial boards in Latin American journals. They compare the representation of women on the editorial boards of several political science journals with the proportion of female faculty members in political science departments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We build upon a research agenda initiated in the U.S. and Europe that analyzes gender disparities, manifested as an imbalance in the presence of women in scientific disciplines (Goastellec and Pekari, 2013;Murphy et al, 2020) and on both the level of production and impact (Goyanes et al, 2024). Specifically, in the field of political science, these studies have shown that women hold lower positions in academic organizations (Elizondo, 2015;Fernández, 2006;Rocha Carpiuc, 2016), are underrepresented as authors or main authors of coauthored papers in the most prestigious academic journals (Candido et al, 2021;Teele and Thelen, 2017), and other areas such as the journal editorial boards (Goldfrank and Welp, 2023).…”
Section: Introductionmentioning
confidence: 99%